2009
DOI: 10.2174/1874372200903010042
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxyacetone and Methods to Improve its Performance as Artificial Tanner

Abstract: Dihydroxyacetone binds to proteins in the stratum corneum of the skin imparting a non-toxic, bronze color to the skin. The resulting pigments are called melanoidins, or brown chromophores. Since the 1980's, improved formulations of sunless tanners are available due to more purified sources of DHA and refinements in the DHA manufacturing process. The color is not removed by simple washing, swimming, or natural perspiration, but it only lasts for 5 to 7 days, as skin cells are continuously being shed. Exfoliatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Beside agricultural importance, sugarbeet plays very important role in industrial area as sunless tanner dihydroxyacetone extracted from sugar beet ( 9 ). For human health, it has good medical potentials for anticancerous activity ( 10 ) and is a good source of antioxidant ( 11 ), aphrodisiac ( 12 ), antidepressant ( 13 ) and organic dyes ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beside agricultural importance, sugarbeet plays very important role in industrial area as sunless tanner dihydroxyacetone extracted from sugar beet ( 9 ). For human health, it has good medical potentials for anticancerous activity ( 10 ) and is a good source of antioxidant ( 11 ), aphrodisiac ( 12 ), antidepressant ( 13 ) and organic dyes ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of DHA in sunless tanning products usually range from 1 to 10% . To take the effect of DHA concentration into consideration, the molar ratios of DHA to AA were set at 1, 2, and 3 with the corresponding final concentrations being 0.3, 0.6., and 0.9 mol/L (≈3, 6, and 9%, respectively) .…”
Section: Methodsmentioning
confidence: 99%
“…21 To take the effect of DHA concentration into consideration, the molar ratios of DHA to AA were set at 1, 2, and 3 with the corresponding final concentrations being 0.3, 0.6., and 0.9 mol/L (≈3, 6, and 9%, respectively). 22 It has been reported that DHA takes 3−12 h to start the tanning reaction with the SC of skin, and the ensuing darkening process continues for 24−72 h. 21 The SC of human skin has a pH gradient from an acidic pH to a neutral pH (4−7), and in most cases, it is slightly acidic with an approximate pH of 5.5. 23 In addition, the normal human skin temperature is around 36 °C, and it can usually tolerate higher temperatures up to 50 °C without being harmed.…”
Section: Introductionmentioning
confidence: 99%
“…The public interest in tanning has grown dramatically since more and more people view the tanned skin as more esthetically pleasing and healthy. , Various ways of tanning have emerged and evolved through the years to become more readily feasible and convenient to use for all consumers, such as natural ultraviolet radiation (UVR), artificial UVR, and sunless tanning products . With the increasing incidence of skin cancer, people’s desire for safer and more efficient tanning methods has made sunless tanning the most popular way. , Sunless tanning products not only produce a durable sun-kissed look without the risks of photodamage but also offer a moderate sun protection factor. , These products come in many forms, such as lotions, mousses, gels, and creams.…”
Section: Introductionmentioning
confidence: 99%